SOCIAL ACCOUNTING / AUDITING BAGI KINERJA SOSIAL PERUSAHAAN (Social Accounting/Auditing for Social Performance of Corporation) - Mu'man Nuryana (Politeknik Kesejahteraan Sosial, 2005)
The core business of corporation, community and community organizations is to achieve some form of social, community or environmental benefit. Financial sustainability or profitability is essential to achieving that benefit, but subsidiary to it. The stakeholder and all the people associated with it or affected by it, need to know if it is achieving its objectives, if it is living upto its values and if those objectives and values are relevant and appropriate. That is what the social accounting process aims to facilitate. Social accounting and audit is a framework which allows a corporation to build on existing documentation and reporting and develop a process whereby it can account for its social performance, report on that performance and draw up an action plan to improve on that performance, and through which it can understand its impact on the community and be accountable to its key .stakeholders. Thus, the essence of this article is therefore: explaining social account and audit for what we do and listening to what others have to say so that future performance can be more effectively targeted at achieving the chosen objectives. This article offers an inclusive ideas for the public, corporation, voluntary and community sectors in supplementing the creation of greater social welfare for all.